Conceptualizing strong sustainable entrepreneurship. Issue 1 (2nd January 2016) - Stål, Herman I.; Bonnedahl, Karl
Abstract : This conceptual article focuses on the environmental dimensions of sustainable development which are essential for satisfying current and future human needs. It assesses ecological economics (EE) as an alternative base for a "strong" version of sustainable entrepreneurship (SE). EE recognizes the biophysical base of economic activity, critical natural capital (non-substitutability) and limits to market valuation and exchange. Contemporary entrepreneurial definitions, however, as well as recent SE framings, pre-suppose that functioning markets will achieve sustainable development. As discussed in this paper, natural processes are non-linear and critical, and as thresholds are impossible to anticipate, markets are unreliable and principally at odds with the objectives of sustainable development. Our proposed alternative constitutes a way forward.